The effectiveness of a rational-emotive intervention on teachers’ unconditional self-acceptance, perfectionism, and pupil control ideology - Samfira, Elena Mirela; Sava, Florin Alin (Frontiers in Psychology, 2023)
The present research aimed to investigate the effectiveness of a Rational Emotive Behavior Therapy (REBT) intervention on in-service teachers. A quasi-experimental 2-group (intervention vs. control) x 3-time (pre, post-test, follow-up) design was applied to explore to what extent the REBT interventions help teachers increase their level of unconditional self-acceptance as the primary outcome and decrease their perfectionism tendencies and pupil control ideology as secondary outcomes. The sample consisted of 100 in-service teachers assigned to either the intervention group (n = 50) or the control group (n = 50). The experimental group received a 6-week intervention program. Every session was held weekly and lasted 90-120 minutes. The Unconditional Self-Acceptance Questionnaire (USAQ) (Chamberlain and Haaga, 2001), Pupil Control Ideology Scale (PCI) (Willower et al., 1967), and Perfectionism Inventory Scale (PI) (Hill et al., 2004) were used to collect data. This study used a mixed model ANOVA 2 X 3 for data analysis. The results indicated that in the experimental group, there was a statistically significant increase in unconditional self-acceptance level from pre-test to post-test, which remains significant at the 6-month follow-up. Likewise, there were no statistically significant differences in unconditional self-acceptance levels between the post-test and 6-month follow-up in the intervention group. These findings prove that REBT interventions effectively increase teachers’ unconditional self-acceptance.